Autonomous Learning Among Arabic Learners: Implications For Tertiary-Level Education - Md Azmi, Nur Afiqah; Mustapha, Nik Hanan; Khalil, 'Ammar (Ijaz Arabi Journal of Arabic Learning, 2025)
As the demand for Arabic proficiency grows in an increasingly interconnected world, fostering autonomous learning becomes essential for students. This study investigates the level of autonomous learning among Arabic language learners in a tertiary context. A quantitative survey is employed using Murase’s (2015) Measuring Instrument for Language Learner Autonomy (MILLA) with a 5-point Likert scale. One hundred forty-four diploma students majoring in Islamic Studies at Universiti Islam Antarabangsa Tuanku Syed Sirajuddin (UniSIRAJ), Malaysia, attempted the questionnaire and was analyzed using SPSS. The results indicate a high level of autonomous learning among the participants, with sociocultural, technical, political-critical, and psychological factors significantly contributing to this autonomy. This study highlights the importance of fostering an environment that encourages autonomous learning and contributes to more effective and engaging Arabic language education. The implications of these findings suggest actionable strategies for educators and institutions to enhance autonomous learning, thereby improving language outcomes for tertiary-level students.